An Analysis of English Proficiency of the Students of Universitas Riau – Indonesia - Ras, Fakhri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2017)
The objectives of this study are to: (1) acknowledge the students’ English competence based on the taken majors and study programs, (2) determine the general English competence (TOEFL Equivalent). The target group of the study is all students who took English language at various faculties and at the same time also enrolled at TOEFL Equivalent at UPT Bahasa Universitas Riau (Language Center). The number of the population is 9.765 the students. Due to the homogenous characters of the population, 20% out of the population (1.953 students) were taken as sample of the research. TOEFL Equivalent compiled by the Language Center of Universitas Riau was used to collect the needed data. Descriptive statistics was operated to compute the data in order to get mean of the TOEFL Equivalent scores. Inferential statistics (Annova) was applied to differentiate the scores of TOEFL Equivalent obtained by various backgrounds of the students (gender, program taken at Universitas Riau, majors at senior high schools, region of their senior high schools, school status and ethnic groups). After analysing the data, it was found that female students’ mean score is higher (405) than the male’s (402); the mean TOEFL score of the study program taken at Universitas Riau in which the English Students is the highest (432) among a lot of study programs; the mean score of the students of Riau Province is higher (420) than the Riau Archipelago Province (401); the mean score of students of private schools is higher (405) than the state schools (404); the mean of TOEFL score of Language and Art is the highest (432) among three majors (natural science, social science and other science). The last is the Chinese / Tionghoa mean of TOEFL score is the highest (438) among existing ethnic groups. The findings suggest that the students of Universitas Riau should be aware of understanding parts of the TOEFL materials like listening, reading, and structure especially in the area of their difficulties.